Decrypting New Age International Capital Flows - Graf von Luckner, Clemens; Reinhart, Carmen M.; Rogoff, Kenneth (World Bank, Washington, DC, 2021)
This paper employs high frequency transactions data on the world’s oldest and most extensive centralized peer-to-peer Bitcoin market, which enables trade in the currencies of more than 135 countries. It presents an algorithm that allows, with high probability, the detection of “crypto vehicle transactions” in which crypto currency is used to move capital across borders or facilitate domestic transactions. In contrast to previous work which has used “on-chain” data, this paper’s approach enables one to investigate parts of the vastly larger pool of “off-chain” transactions. Finding that, as a conservative lower bound, over 7 percent of the 45 million trades on the exchange we explore represent crypto vehicle transactions in which Bitcoin is used to make payments in fiat currency. Roughly 20 percent of these represent international capital flight/flows/remittances. Although this work cannot be used to put a price on cryptocurrencies, it provides the first systematic quantitative evidence that the transactional use of cryptocurrencies constitutes a fundamental component of their value, at least under the current regulatory regime.